THE IMPACT OF THE WORK ENVTHE IMPACT OF THE WORK ENVIRONMENT ON THE DEVELOPMENT OF ADAPTIVE PERFORMANCE THE CASE STUDYIRONMENT ON THE DEVELOPMENT OF ADAPTIVE PERFORMANCE THE CASE STUDY - Slimani, Ilyes; Douli, Lakhdar (International Journal For Research In Business, Management And Accounting, 2021)
The adaptive performance in the work environment demonstrates adaptation and understanding of change and changes in the enterprise climate and the nature of the business. This study, which was conducted at the level of the Algerie Telecom Company Foundation Bechar branch aims to highlight the relationship and influence between the various aspects of the work environment and elements of adaptive performance.